2018
DOI: 10.1093/mnras/sty2671
|View full text |Cite
|
Sign up to set email alerts
|

Binary asteroseismic modelling: isochrone-cloud methodology and application toKeplergravity mode pulsators

Abstract: The simultaneous presence of variability due to both pulsations and binarity is no rare phenomenon. Unfortunately, the complexities of dealing with even one of these sources of variability individually means that the other signal is often treated as a nuisance and discarded. However, both types of variability offer means to probe fundamental stellar properties in robust ways through asteroseismic and binary modelling. We present an efficient methodology that includes both binary and asteroseismic information t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 91 publications
(156 reference statements)
3
91
0
Order By: Relevance
“…We see that estimation of the convective core mass and size is well achieved, despite the absence of predictive power for the core overshoot parameter. This is the same conclusion as found by Johnston et al (2019) for three gravity-mode pulsators in close binaries and points to a strong probing power of dipole gravity modes (through Π 0 ) to assess convective core properties. When we compare the four stars closest to ZAMS, we notice that the two stars with a lower f rot have more massive and larger convective cores than the two faster rotating stars.…”
Section: Parameter Estimation From π 0 T Eff and Log Gsupporting
confidence: 89%
See 2 more Smart Citations
“…We see that estimation of the convective core mass and size is well achieved, despite the absence of predictive power for the core overshoot parameter. This is the same conclusion as found by Johnston et al (2019) for three gravity-mode pulsators in close binaries and points to a strong probing power of dipole gravity modes (through Π 0 ) to assess convective core properties. When we compare the four stars closest to ZAMS, we notice that the two stars with a lower f rot have more massive and larger convective cores than the two faster rotating stars.…”
Section: Parameter Estimation From π 0 T Eff and Log Gsupporting
confidence: 89%
“…Both overshooting prescriptions suggest that the amount of mixing in the radiative zone, D mix , has only a modest effect on Π 0 , as already reflected in Fig. 1 (see also table 2 in Johnston et al 2019). However, we expect D mix to have some effect on Π 0 (Van Reeth et al 2015b) and mainly on the mode trapping, as was shown from forward modelling of g modes in the Kepler B-type pulsator KIC 10526294 .…”
Section: Linear Statistical Model For πmentioning
confidence: 56%
See 1 more Smart Citation
“…On this figure we show the positions of the stars in terms of luminosity and effective temperature. For illustrative purposes, we include evolutionary tracks computed by Johnston et al (2019) with the MESA stellar evolution code (Paxton et al 2011(Paxton et al , 2013(Paxton et al , 2015(Paxton et al , 2018. These are non-rotating tracks with Z = 0.014, an initial hydrogen abundance X ini = 0.71, diffuse exponential overshooting parameter f ov = 0.020, the Asplund et al (2009) heavy element mixture, and the standard MESA opacity tables that incorporate different sources (Paxton et al 2011).…”
Section: Idmentioning
confidence: 99%
“…In the best cases, these systems offer dynamical mass and radius estimates to better than one per cent (Torres et al 2010). Such precise measurements combined with the powerful constrains of co-evolution and identical initial chemical composition have allowed the thorough investigation of the importance of rotation in stellar evolutionary theory (Brott et al 2011a,b;Ekström et al 2012Ekström et al , 2018de Mink et al 2013;Schneider et al 2014), the calibration of pre-through post-main-sequence evolution (Torres et al 2013;Higl & Weiss 2017;Beck et al 2018a;Kirkby-Kent et al 2018), the critical investigation of magnetic fields in stars (Takata et al 2012;Grunhut et al 2013;Torres et al 2014b;Pablo et al 2015;Kochukhov et al 2018;Wade et al 2019), the calibration of distances (Guinan et al 1998;Ribas et al 2000aRibas et al , 2005Hensberge et al 2000;Bonanos et al 2006;Pietrzyński et al 2013;Gallenne et al 2016;Suchomska et al 2019), the investigation of abundances and rotational velocities (Pavlovski & Hensberge 2005;Pavlovski & Southworth 2009;Pavlovski et al , 2018Simón-Díaz et al 2017), and the calibration of asteroseismic modelling (De Cat et al 2000, 2004; Aerts & Harmanec 2004;Schmid et al 2015;Schmid & Aerts 2016;Beck et al 2018a,b;Johnston et al 2019). Additionally, the development of such precise measurements has led to the reported systematic discrepancy between masses obtained via dynamics or empirical spectral relations and fitting theoretically calculated evolutionary tracks…”
Section: Introductionmentioning
confidence: 99%